2012
DOI: 10.1590/s1516-14392012005000103
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Al-Si-X system by different cooling rates and heat treatment

Abstract: The solidification behavior of the Al-12.6% Si (A1), the hypereutectic Al-20%Si (A2) and the Al-20%Si-1.5% Fe-0.5%Mn (A3) (in wt. (%)) alloys, at different cooling rates is reported and discussed. The cooling rates ranged between 0.93 °C/s and 190 °C/s when cast in sand and copper wedge-shaped molds, respectively. A spheroidization heat treatment was carried out to the alloys in the as-cast condition at 540 °C for 11 hours and quench in water with a subsequent heat treatment at 170 °C for 5 hours with the purp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 23 publications
0
6
1
Order By: Relevance
“…On the other hand, the minimum UTS (180 ± 2.5 MPa) and elongation (3.4%) values were obtained in the Al-20Si-1.5Fe-0.7Mn alloy. The mechanical properties obtained in this study are higher than the results reported in a previous work 16 . The increase of the UTS and the elongation (%) values could be attributed to the refinement of the primary Si due to combined effect of rapid solidification and the addition of the phosphorous compound.…”
Section: Mechanical Propertiescontrasting
confidence: 85%
“…On the other hand, the minimum UTS (180 ± 2.5 MPa) and elongation (3.4%) values were obtained in the Al-20Si-1.5Fe-0.7Mn alloy. The mechanical properties obtained in this study are higher than the results reported in a previous work 16 . The increase of the UTS and the elongation (%) values could be attributed to the refinement of the primary Si due to combined effect of rapid solidification and the addition of the phosphorous compound.…”
Section: Mechanical Propertiescontrasting
confidence: 85%
“…As it has been reported, the mechanical properties of pure aluminum can be improved when small amounts of second phases with high elastic modulus (similar to those used in composite materials) are formed by the addition of copper, silicon, nickel and other elements (i.e. Al 2 Cu, Al 3 Ni, Al 3 Ti, Al 13 Fe 4 ) [1][2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 89%
“…Furthermore, heat transfer between ingot, mould and environment should be sufficient to prevent excessive grain growth and allow a sufficiently thick, solid shell to form and the mushy zone (where solid and liquid coexist in the solidifying ingot) to develop a substantial coherent volume, i.e., a solid matrix substantial enough to bear the extraction load [42][43][44] . Application of a conductive coating (e.g., graphite) or use of a highly conductive alloy as mould material could help to accelerate solidification 45,46 .…”
Section: Methodsmentioning
confidence: 99%